Grassroots football development in Japan: A case study / Masahiro Sugiyama - Masahiro , Sugiyama (2019)
Grassroots football is a fundamental part of the structure that underpins top-level football. It is gaining importance at various levels of football with programmes run by global, continental, regional, national, and local associations. However, there has been very little research on the development and significance of football at the lower level. Therefore, the main aim of the study is to examine the mechanisms of successful grassroots football programmes by identifying determinants, understanding their contexts, and analysing any difficulties in order to overcome their obstacles. Japan is selected as a case study for this research because it is one of the most successful countries in Asia in terms of grassroots football development. There has been a 20% growth in the number of registered players under 12 years old from 1985 (231,036 players) to 2017 (279,134 players). The steady increase is a result of the Japan Football Association (JFA)’s emphasis on grassroots football (especially the 6-10 years old age group) since 2003. The focus of this project is on initiatives by prefectural football associations because they are the key stakeholders in implementing development programmes in Japan. In Study 1, a survey was used to examine the current status of 47 prefectural football associations in terms of grassroots football development. It was distributed to those persons in charge of grassroots football development in each of the 47 prefectural football associations, and 24 associations responded. Based on the results of the survey, the prefectural football associations were ranked in terms of grassroots football development. In Study 2, a total of 33 face-to-face semi-structured interviews were conducted from a cohort which included Football Association (FA) General Secretaries, FA Youth Directors, FA Kids Committee Chairmen, coaching instructors, coaches, and referee from the 10 most successful prefectural football associations. Thematic analysis was used to analyse the interviews using the QSR NVivo 10 qualitative data analysis software. A total of 14 determinants for successful grassroots football development were identified. The determinants were examined and four thematic aspects were selected, namely governance, stakeholders, programmes, and strategy. The results of the study also demonstrated the obstacles that stakeholders have faced in implementing grassroots football programmes, and the strategies taken to overcome the obstacles. Finally, a house model was developed to help understand the mechanisms of successful grassroots football programmes in Japan. Although some limitations were recognized, the findings from the study are promising and will help stakeholders involved in grassroots football development to better comprehend the mechanisms of grassroots football development programmes, which is an important step in the process of designing successful programmes at the lower levels of football.